2012
DOI: 10.1590/s0103-50532012000600004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of the alkaline decomposition of potassium arsenojarosite

Abstract: Uma amostra de arsenojarosita de potássio foi sintetizada e completamente caracterizada. A amostra obtida é uma solução sólida de arsenojarosita de potássio, cuja fórmula aproximada é [K 0,75 3.66 ]. The decomposition process in alkaline medium was studied in the induction and progressive conversion periods, and the reaction order and activation energy were determined for each case. Under the used experimental conditions, results are consistent with the spherical particle model with decreasing core and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…The dependence of the energy parameter ( E a ) is lower in the progressive conversion period compared to the induction period by difficulty of forming active sites and subsequently lead to propagation of the reaction through the reaction front requiring more energy in this period. With respect to other decomposition studies in NaOH medium of synthetic jarosites as arsenojarosite , mercury jarosite is more stable because the activation energy values are higher; however, compared to the potassium and sodium arsenojarosite is less stable due to the high‐energy demand that they need . Another variable studied is the particle size that affects the reaction rate since the smaller particles are rapidly decomposed and vice versa, because the reaction usually progresses rapidly as the surface area of the solid increases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of the energy parameter ( E a ) is lower in the progressive conversion period compared to the induction period by difficulty of forming active sites and subsequently lead to propagation of the reaction through the reaction front requiring more energy in this period. With respect to other decomposition studies in NaOH medium of synthetic jarosites as arsenojarosite , mercury jarosite is more stable because the activation energy values are higher; however, compared to the potassium and sodium arsenojarosite is less stable due to the high‐energy demand that they need . Another variable studied is the particle size that affects the reaction rate since the smaller particles are rapidly decomposed and vice versa, because the reaction usually progresses rapidly as the surface area of the solid increases.…”
Section: Resultsmentioning
confidence: 99%
“…The jarosite process offers the advantage of removing the iron by the high‐efficiency precipitation of the solution with relatively low losses of divalent base metals such as zinc, cadmium and copper . The particularity of these compounds is that they may have different substitutions in the structure of jarosite, working as a means of inertization incorporating elements of environmental importance, such as Tl + , Cr(VI), As(V), ½Pb 2+ , ½Cd 2+ and ½Hg 2+ reducing its impact on the environment . One of the less well studied jarosite‐type compounds is mercury jarosite Hg 0.5 Fe 3 (SO 4 ) 2 (OH) 6 , synthesized by Dutrizac and Kaiman in 1976 making it possible to incorporate 14.62 wt% mercury.…”
Section: Introductionmentioning
confidence: 99%
“…They propose that near the point of zero charge of the jarosite, the dissolution may be controlled by water attack. Flores et al 48 and Reyes et al 50 found orders of reaction of n = 0 at low [OH − ], which is indicative of inexistent dependence on the reaction medium. In the present work, it is proposed that when there is no dependence on the reaction medium [OH − ], the attack towards the solid particles is done by water, 43 which results in orders of reaction equal to zero and, therefore, much slower reaction rates independent of [OH − ].…”
Section: Synthesis and Characterizationmentioning
confidence: 98%
“…This kind of behavior is similar to that previously studied in synthetic jarosites. 29,32,35,48 Decomposition reactions are usually stoichiometric, but in this case the reaction is incongruous, as the molar fractions do not coincide with the conducted calculations. The molar fraction of K + and SO 4 2− in aqueous solution is very close to the molar fraction in solids.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Jarosites have the capability to incorporate elements of environmental concern-such as Pb 2+ , As(V), Cr(VI), Cd 2+ , and even Hg 2+ -into their structure. Patiño Asta et al 2009 have conducted the most recent studies regarding the incorporation of arsenic into the structure of jarosite-type compounds under different conditions of pH, temperature, and particle size [29][30][31][32][33]. Dutrizac and Kaiman, 1976, were the first researchers to synthesize jarosite-type compounds with mercury, which was achieved by incorporation of 14.62 wt.…”
Section: Introductionmentioning
confidence: 99%